Intraspecific variation in Janzen–Connell effect is mediated by stress and plant–soil feedbacks - Libing Pan; J. Aaron Hogan; Xiaoyang Song; Wenfu Zhang; Huaze Zhou; Zhonglin Chen; Jie Yang; Min Cao (Ecology and Evolution)
Abstract Janzen–Connell (JC) effects, hypothesized to be partially driven by negative plant–soil feedbacks (PSFs), are considered to be a key mechanism that regulates tropical forest plant diversity and coexistence. However, intraspecific variation in JC effects may weaken this mechanism, with the strength of PSFs being a potentially key variable process. We conducted a manipulated experiment with seedlings from two populations of Pometia pinnata (Sapindaceae), a tropical tree species in southwest China. We aimed to measure the intraspecific difference in PSF magnitude caused by inoculating the soil from different P. pinnata source populations and growing seedlings under differing light intensity and water availability treatments, and at varying plant densities. We found negative PSFs for both populations with the inoculum soil originating from the same sites, but PSFs differed significantly with the inoculum soil from different sites. PSF strength responded differently to biotic and abiotic drivers; PSF strength was weaker in low moisture and high light treatments than in high moisture and low light treatments. Our study documents intraspecific variation in JC effects: specifically, P. pinnata have less defenses to their natively‐sourced soil, but are more defensive to the soil feedbacks from soil sourced from other populations. Our results imply that drought and light intensity tended to weaken JC effects, which may result in loss of species diversity with climate change.